Debt, Deficits, and Age-Specific Mortality - Faruqee, Hamid (IMF Working Papers; Working Paper ;, 2002)
This paper develops an overlapping agents model with age-specific mortality rates. The analytical framework also nests Blanchard's (1985) "perpetual youth" model as a special, though perhaps not realistic, case. With age specific mortality rates, youth is "fleeting." Using standard hyperbolic functions, the model with fleeting youth is able to closely replicate the empirical relation between age and mortality. The comparative implications for deficit finance are also examined and age-specific mortality is shown to alter the non-Ricardian properties of the model.